Self-Organization in Multi-Agent Systems Based on Examples of Modeling Economic Relationships between Agents - Krolikowski, Rafal; Kopys, Michal; Jedruch, Wojciech (Frontiers in Robotics and AI, 2016)
The goal of the research was to observe and analyze self-organization patterns in Multi-Agent Systems (MAS) by modeling basic economic relationships between agents forming a closed loop of relations necessary for their survival. The paper describes a worked-out MAS including an example of a production cycle and used economic rules. A special focus is put on behavior rules and decision systems of an individual agent such as: product advertising, price and purchase negotiations, dealing in the context of limited resources, and time constraints to make a decision. The MAS was implemented in a dedicated environment, and a number of simulations were carried out. The paper reports some of the recorded self-organization patterns, and their dynamics over time in terms of their spatial arrangement or mutual relations (e.g., bargain price, market shares, etc.), provides analysis and discussion, and shows the direction of further research.